1977
DOI: 10.1002/ijc.2910200503
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of infectious EB virus from the epithelial tumour cells of nasopharyngeal carcinoma

Abstract: Evidence of herpesvirus replication has been found by light and electron microscopy in the malignant epithelial cells of two out of six nasopharyngeal carcinomas (NPC) examined directly after growth in nude mice to eliminate non-malignant infiltrating cells. The agent has been identified as EB virus by immunofluorescence tests for EB virus capsid antigen, and has been shown to be biologically active by its ability to infect and transform foetal cord blood lymphocytes. Lymphoblastoid cell lines which express th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

1979
1979
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(25 citation statements)
references
References 37 publications
(41 reference statements)
2
22
1
Order By: Relevance
“…It is also observed that there is a ''spike'' in circulating EBV DNA levels immediately after the first treatment (5), suggesting an alternate hypothesis of the activation of EBV into a lytic phase. This hypothesis is supported by the detection of infectious EBV in NPC cells (26), the presence of the linear form of the EBV genome suggestive of a productive lytic cycle (27), and observations of BRLF1 expression in NPC biopsy samples along with circulating BRLF1 antibodies in NPC patients (28). Our current study supports the concept that EBV activation could contribute to the observed increased levels of circulating EBV after treatment.…”
Section: Discussionsupporting
confidence: 84%
“…It is also observed that there is a ''spike'' in circulating EBV DNA levels immediately after the first treatment (5), suggesting an alternate hypothesis of the activation of EBV into a lytic phase. This hypothesis is supported by the detection of infectious EBV in NPC cells (26), the presence of the linear form of the EBV genome suggestive of a productive lytic cycle (27), and observations of BRLF1 expression in NPC biopsy samples along with circulating BRLF1 antibodies in NPC patients (28). Our current study supports the concept that EBV activation could contribute to the observed increased levels of circulating EBV after treatment.…”
Section: Discussionsupporting
confidence: 84%
“…Indeed some NPC biopsies appear to express transcripts usually associated with entry of cells into the productive cycle Tugwood et al, 1987) and the passage of NPC cells in nude mice in some cases leads to full virus replication in a small proportion of the cells (Trumper et al, 1977). However, in the present experiments we could find no detectable expression of lytic cycle antigens in NPC biopsies using either a selected human serum or the EA(D)-specific MAb R3 (Fig.…”
Section: Discussioncontrasting
confidence: 53%
“…A more likely explanation for the tumor is that long-term passage of this tumor in vivo has resulted in expression alterations, including up-regulation of genes that break the latent expression pattern. There is indeed evidence in the literature that EB virus can be isolated from NPC xenografts (40). However, cross-hybridization cannot be totally excluded in that long exposures with the H-242 probe also showed some hybridization to the 5-kb rRNA.…”
Section: Resultsmentioning
confidence: 99%